coastDat3 COSMO-CLM MERRA2 ... - Petrik, Ronny; Geyer, Beate (World Data Center for Climate (WDCC) at DKRZ, 2021)
Project: open feed-in time series based on a Renewable Energy Database - The dataset was produced in the framework of the project openFRED. The data are dedicated to force energy system models, i.e. relevant parameters for wind energy (gust estimates), for solar energy (direct normal irradiation) and hydropower (runoff). The project was founded by Bundesministeriums für Wirtschaft und Energie, FKZ: 0324006B. Summary: This is an atmospheric hindcast for Western Europe and the North Atlantic using COSMO-CLM version 5.0 with spectral nudging from 2002-2017. MERRA2 reanalysis data are used as forcing. Additionally transient and monthly aerosol data of the MACv2 climatology are prescribed. The model uses a rotated grid with 566 x 481 grid points and a grid point distance of 0.0625 degrees, the rotated North pole is located at 162.0 W, 39.25 N. The published data excludes the sponge zone and have 526 x 441 grid points. In rotated coordinates the published simulation data extends from 22.64 W to 10.18 E, 11.2 S to ...